Developing an English Students Workbook for Islamic University Students - Mukhlisin, Mukhlisin (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2024)
This study aims to develop and evaluate an English workbook specifically designed for Islamic university students to enhance their language proficiency, focusing on pronunciation, fluency, and academic writing. The workbook integrates culturally relevant content and terminology related to Islamic studies, catering to the unique linguistic needs of these students. A quasi-experimental design was employed, involving an experimental group (n=30) and a control group (n=30) of Islamic university students. The experimental group used the newly developed workbook, while the control group followed traditional learning methods. Data were collected through pretests and posttests on pronunciation, fluency, and writing skills. The results indicated a significant improvement in the experimental group's language skills, particularly in pronunciation and fluency, compared to the control group. The study demonstrates the effectiveness of a specialized English workbook in improving language skills among Islamic university students, highlighting the importance of culturally tailored materials in English for Specific Purposes (ESP) learning. Further research is suggested to explore the long-term impact of such workbooks and to examine the integration of interactive and communicative teaching methods for more comprehensive language acquisition.